Les multiples facettes des inégalités écologiques - Lionel Charles; Cyria Emelianoff; Cynthia Ghorra-Gobin; Isabelle Roussel; François-Xavier Roussel; Helga-Jane Scarwell (Développement Durable et Territoires)
The notion of ecological inequalities is understood in very different ways depending on different cultural contexts. In the United States, where it has first developed, its only meaning is in an action perspective. The idea is to lean on degraded environmental conditions to strengthen the claims of unfavoured communities or ethnical groups. In Europe, it meets the more global notion of populations specifically exposed to risks or contaminating substances, or benefitting from weak quality surroundings. Policies, environmental situations and their health implications can meet and thus reinforce already identified social inequalities.